Hydrolysis profile of gadung (dioscorea hispida dennst) starch to glucose using alpha amylase enzyme - Utari Agustina; Abu Hasan; Indah Purnamasari (Jurnal Teknik Kimia, 2024)
Indonesia is an agrarian Country that has abundant natural resources. It has potential to be used as industrial raw materials such as sugar reduction from starch. Gadung, which is abundant in Gandus and it can be monitored for its presence in the dry season, is one source of starch. The aims of this research is to obtain glucose with a high yield percentage, to know the optimum concentration of α-amylase enzyme to hydrolysis gadung starch into glucose, and to know the relationship between hydrolysis time and concentration the glucose formed by the addition of the enzyme variation. The implementation of the research is carried out in three stages, first is preparation of raw materials, hydrolysis of gadung starch into glucose enzymatically, and analysis of glucose level using the UV-Vis spectrophotometry with Nelson reaction. The free variables used are the time variation of hydrolysis 0, 10, 20, 30, 40, 50 minutes and alpha amylase enzyme 1 %, 2 %, 3 % b/v. The optimum hydrolysis results on this study were at 1 % b/v enzyme variation, 10 minutes hydrolysis time, and a temperature of 90 oC. The yield of glucose concentration is 255.35 ppm. From this reseach, it is known that the longer the starch hydrolysis takes place, the observed glucose tends to experience in fluctuative consentration caused by the increase of α- amylase enzyme variations.